2008
DOI: 10.1161/circulationaha.106.678789
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation of Atrial Fibrillation

Abstract: Background-Several approaches have been developed for radiofrequency catheter ablation of atrial fibrillation, but the correct intraprocedural end point is still under debate, and few data exist about the destiny of ablation lesions over time. The aim of the present study was to evaluate the long-term maintenance of intraprocedural end points of ablation procedures. Methods and Results-Inclusion criteria were (1) a previous ablation procedure of pulmonary vein (PV) encircling performed for drug-refractory pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 34 publications
2
41
2
Order By: Relevance
“…On the other hand, it has been recently reported that there are no statistically significant differences in the persistence of PV disconnections in the patients with and without recurrence after an AF ablation procedure, 17 although that was not demonstrated in the present study. One possibility that may explain the results of these 2 studies is that recovery of the electrical connections happens to occur in the arrhythmogenic PVs in the patients with AF recurrence, whereas it does not occur in the arrhythmogenic PVs in the patients without AF recurrence.…”
Section: Parasympathetic Attenuation and Af Recurrence After Scacontrasting
confidence: 94%
“…On the other hand, it has been recently reported that there are no statistically significant differences in the persistence of PV disconnections in the patients with and without recurrence after an AF ablation procedure, 17 although that was not demonstrated in the present study. One possibility that may explain the results of these 2 studies is that recovery of the electrical connections happens to occur in the arrhythmogenic PVs in the patients with AF recurrence, whereas it does not occur in the arrhythmogenic PVs in the patients without AF recurrence.…”
Section: Parasympathetic Attenuation and Af Recurrence After Scacontrasting
confidence: 94%
“…Electrotonic coupling may interfere with the success of therapeutic interventions, such as atrial ablation, by causing scars to become "electrically transparent" with time (perhaps, in particular, between ablation points, where scars are most narrow). Such "disappearance" of intraprocedurally confirmed lesions seems to occur in a majority of atrial ablation patients (8). Although atrial ablation lines, placed to electrically separate adjacent muscle regions, may perhaps be discontinuous to begin with (even if, intraprocedurally, block is achieved), de novo formation of electrical conduction across continuous and fully transmural scars after surgery has also been reported (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Possible functionality of connexin-based junctions was indicated in rabbit atrium, where dye diffusion between heterotypic cell types has been reported (6), and in mouse ventricle, where fibroblast-specific conditional connexin 43 knockout reduced transmission of injected current from healthy to scarred tissue (7). A number of clinical observations, such as transscar electrical conduction after atrial ablation (8) or surgical repair of congenital heart defects (9) and transplantation (10), in addition to experimental findings of electrical conduction into postinfarct (11) and cryoinjury (7) scars and along implanted tissue grafts (12,13) would be in keeping with a (passive) contribution by nonmyocytes to cardiac AP conduction. Functional heterocellular electrotonic coupling thus far has been shown conclusively in vitro only [where it is aided by phenotype conversion and connexin overexpression of cultured fibroblasts (14)(15)(16)(17)].…”
mentioning
confidence: 99%
“…31 The other study reported a crucial fact that PV disconnection persisted in only ~40% of the previously isolated PVs even in patients with stable maintenance of sinus rhythm. 32 These data suggest that the presence of an arrhythmogenic substrate in addition to PV reconnection makes the atria more susceptible to recurrent AF than does PV reconnection alone. If one applies the results from the present study to this notion, the fluctuation of magnetic strength in the RA might reflect the presence of an arrhythmogenic substrate.…”
Section: Mechanism Of Af Recurrence After Ablationmentioning
confidence: 85%